Copper-cobalt modified photocathode, preparation thereof and application of copper-cobalt modified photocathode in photoelectrocatalysis of urea synthesis
By constructing a copper-cobalt double-single-atom cladding layer on the surface of Cu2O nanorods, the problems of Cu2O photocathode are easily corroded and the low yield of catalytic urea are solved, and more efficient photoelectrocatalytic urea synthesis is achieved, improving yield and corrosion resistance.
Patent Information
- Application Number
- CN202411742464.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
Cu2O is susceptible to photocorrosion in solution as a photocathode, and the yield is low when catalyzing urea, and the co-reduction process of CO2/NO3-bimolecules is slow, resulting in the potential required for the actual urea synthesis and consumes a lot of secondary energy.
The copper-cobalt double single atom coating layer is constructed on the surface of Cu2O nanorods to improve the corrosion resistance of the Cu2O photocathode and improve the efficiency of catalytic CO2/NO3-reduction urea through the dual active center.
The corrosion resistance and catalytic efficiency of Cu2O photocathode are significantly improved, the yield and Faraday efficiency of urea are improved, the input of electrical energy is reduced, and more efficient photoelectrocatalytic urea synthesis is achieved.
Smart Images

Figure CN119530843A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrode materials, and in particular to a copper-cobalt modified photocathode and its preparation and application in photoelectrocatalytic urea synthesis. Background Art
[0002] Urea (CO(NH2)2), an amide chemical, has a wide range of applications in medicine, industry, and agriculture, but its industrial production is an energy-intensive and highly polluting process using ammonia (produced under high temperature and high pressure conditions) and carbon dioxide (CO2) as raw materials. Therefore, there is an urgent need to select a suitable nitrogen source and develop a green and sustainable urea synthesis method under mild conditions.
[0003] In recent years, researchers have used electrocatalytic CO2 / NO3 - Co-reduction coupling realizes the green synthesis of urea, but due to the slow kinetics of bimolecular co-adsorption and reduction coupling, the potential required for the actual synthesis of urea is much higher than the theoretical potential (0.81V relative to the standard hydrogen electrode), which consumes a lot of secondary energy. The photoelectric catalytic system integrates semiconductors and catalysts into electrodes, and can use the photovoltage generated by the semiconductor absorbing sunlight to compensate for the overpotential of urea synthesis, thereby reducing the input of electrical energy and providing a new idea for the efficient synthesis of urea. Therefore, the photoelectric catalytic CO2 / NO3 - Co-reduction coupling to produce urea is a new and effective strategy for the green and sustainable production of urea.
[0004] The photocathode material is photoelectrocatalytic CO2 / NO3 - Co-reduction coupling is the core of urea. The photocathode material for efficient photocatalytic urea synthesis should have strong light absorption ability, suitable energy band structure, stability and surface energy to efficiently catalyze CO2 / NO3 - Co-reduction coupling to urea. p-type semiconductor Cu2O, cheap, band gap ~2.0eV, theoretical photocurrent up to 14.7mA / cm 2 , is a widely used photocathode material, and its conduction band potential energy satisfies both CO2 and NO3 - The reduction potential of CO2 / NO3 - However, studies have found that the equilibrium potential of Cu2O oxidation and reduction in solution is between its forbidden bands, and it is easy to be reduced by electrons in the conduction band and oxidized by holes in the valence band. Therefore, Cu2O is severely photocorroded when used as a photocathode, which will restrict its practical application in photocatalytic urea synthesis. In addition, CO2 / NO3 - It is difficult for the two molecules to co-adsorb on the same active surface due to their electrical differences, and the co-reduction process of the two molecules involves multiple electron / proton transfer processes. The by-products are complex and diverse, and the reduction process is accompanied by the occurrence of hydrogen evolution competition reactions, resulting in a low urea yield. Summary of the invention
[0005] In view of the problem that Cu2O as a photocathode is susceptible to photocorrosion in the prior art and has a low yield when catalyzing the synthesis of urea, the present invention provides a copper-cobalt modified photocathode and its preparation and application in photoelectrocatalytic urea synthesis to solve the above problems. The present invention constructs a copper-cobalt double single-atom coating layer on the surface of Cu2O nanorods to improve the corrosion resistance of the Cu2O photocathode and also utilizes double active centers to improve the catalytic performance of the Cu2O photocathode in CO2 / NO3 - Efficiency of urea reduction.
[0006] The technical solution of the present invention is: In a first aspect, the present invention provides a copper-cobalt modified photocathode, which uses a Cu2O@Cu1Co1 / NC catalytic electrode material.
[0007] In a second aspect, the present invention provides a method for preparing the above-mentioned copper-cobalt modified photocathode, comprising the following steps: (1) Use clean copper sheet, platinum sheet and Ag / AgCl electrode as working electrode, counter electrode and reference electrode respectively, use 3M KOH solution as electrolyte, and conduct the test at 10 mA / cm 2 The electrochemical oxidation was carried out at a constant current for 10 min. After the electrolysis, a blue Cu(OH)2 / Cu sheet was obtained, which was washed with distilled water and dried in a vacuum drying oven for later use. (2) The blue Cu(OH)2 / Cu sheet prepared above was first placed in a tube furnace and calcined in air at 180°C for 1 hour to convert into CuO, and then annealed at 600°C for 4 hours in an argon flow (purity 99.9995%) atmosphere; the temperature was naturally lowered to obtain a Cu2O / Cu sheet; (3) The Cu2O / Cu sheet prepared above was immersed in 20 mL of an aqueous solution containing 0.1 M dopamine hydrochloride, the pH was adjusted to 9 with a 1.0 M KOH solution, 0.01 M Cu(NO3)2 and 0.01 M Co(NO3)2 were added to the solution, and the solution was allowed to stand for 10 min to form a film; the Cu2O / Cu sheet coated with copper-cobalt dopamine was taken out, washed and dried, and placed in a tubular furnace, and calcined at 500 °C in an argon atmosphere for 1 h to obtain Cu2O@Cu1Co1 / NC.
[0008] Furthermore, in step (1), the copper sheet is sequentially placed in acetone, ethanol, secondary water, and hydrochloric acid solution for ultrasonic cleaning for 15 minutes; after cleaning, the copper sheet is rinsed with distilled water for 3 times to clean the hydrochloric acid solution remaining on the surface, and then placed in a vacuum drying oven to dry for use.
[0009] Furthermore, the molar ratio of Cu(NO3)2 to Co(NO3)2 is 1:10~10:1.
[0010] The clean copper sheet refers to the copper sheet purchased by the following treatment: first, the copper sheet is cut into a rectangle of 3 cm × 1 cm so as to be used as a supporting electrode later; the cut copper sheet is placed in acetone, ethanol, secondary water, and hydrochloric acid solution (V 水 :V 盐酸 =3:1) ultrasonic cleaning for 15 minutes to remove organic matter, oxide layer and other impurities that may exist on the surface of the substrate; after the ultrasonic cleaning is completed, rinse the copper sheet with distilled water for 3 times to clean the hydrochloric acid solution remaining on the surface, and place it in a vacuum drying oven to dry for use.
[0011] In a third aspect, the present invention provides an electrolytic cell comprising Cu2O@Cu1Co1 / NC, wherein a Cu2O@Cu1Co1 / NC nanorod array grown on the surface of a copper sheet is used as a photocathode, a platinum sheet is used as an anode, an Ag / AgCl electrode is used as a reference electrode, and a mixture of 0.1M KHCO3 and 0.05M KNO3 containing CO2 is used as an electrolyte.
[0012] In a fourth aspect, the present invention provides a method for catalyzing CO2 / NO3 using the electrolytic cell. - The application of reductive coupling to urea, in which a 300W xenon lamp with an AM1.5G filter was used to simulate sunlight (light intensity 100mW cm -2 ), test the linear scan curve (LSV) under the condition of illumination and without illumination, and select the appropriate bias voltage range according to the LSV under illumination and without illumination, and perform constant potential photoelectrolysis under different bias voltages. Subsequently, we used three quantitative test methods, colorimetry, high performance liquid chromatography, and nuclear magnetic resonance 1H spectroscopy, to detect the blank electrolyte (0.1M KHCO3) and the presence of CO2 / NO3 - Urea products after photoelectrolysis of (0.05M KNO3) electrolyte at 0.1Vvs.RHE for 2h.
[0013] The embodiment of the present invention provides a method for preparing a Cu2O photocathode modified with a copper-cobalt double single-atom double-effect layer and applies it to photoelectrocatalytic urea synthesis. The Cu2O@Cu1Co1 / NC catalytic material with a nanorod-like structure is designed and synthesized, which has low cost and high active area. The material is applied to photoelectrocatalytic CO2 / NO3 - When the co-reduction coupling is used to prepare urea, a high urea yield and a high Faradaic efficiency are exhibited. In the entire reaction process, the device is simple and has broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0015] Figure 1 1 is a scanning electron microscope (SEM) image of Cu(OH)2 and Cu2O prepared in Example 1 of the present invention, wherein (a) is Cu(OH)2 and (b) is Cu2O.
[0016] Figure 2 The SEM and TEM images of Cu2O@Cu1Co1 / NC prepared in Example 1 of the present invention are shown in FIG. Figure 2 (a) is the SEM image, Figure 2 (b) is a transmission electron microscope (TEM) image.
[0017] Figure 3 It is the X-ray diffraction (XRD) pattern of Cu(OH)2, Cu2O and Cu2O@Cu1Co1 / NC nanorod arrays prepared in Example 1 of the present invention.
[0018] Figure 4 This is an X-ray photoelectron spectrum (XPS) graph of Cu2O@Cu1Co1 / NC prepared in Example 1 of the present invention.
[0019] Figure 5 This is a high-angle annular dark field image-scanning transmission electron microscope (HAADF-STEM) image of Cu2O@Cu1Co1 / NC prepared in Example 1 of the present invention.
[0020] Figure 6 (a) is a photo of the Cu2O@Cu1Co1 / NC photoelectric testing equipment prepared in Example 1 of the present invention.
[0021] Figure 6 (b) is the linear voltammetric scanning curve (LSV) of Cu2O@Cu1Co1 / NC prepared in Example 1 of the present invention when illuminated or not.
[0022] Figure 7 (a) is the standard curve for the colorimetric determination of urea content. The photo on the upper left shows the photoelectrolysis of Cu2O@Cu1Co1 / NC under 0.1V vs. RHE bias in the presence of CO2 / NO3 - Color photos of the electrolyte after 2 hours of photoelectrolysis. The lower right corner shows the presence of CO2 / NO3 - The raw material electrolyte solution was photoelectrolyzed for 2 hours and then diluted 1 / 10 for color development.
[0023] Figure 7(b) The upper and lower figures are respectively HPLC and NMR tests for the presence of CO2 / NO3 - Results of the electrolyte with or without electrolysis at 0.1V vs.RHE bias for 2h.
[0024] Figure 8 The Cu2O prepared in Example 1 of the present invention and the Cu2O@Cu1Co1 / NC prepared in Example 1 of the present invention were used as photocathodes, respectively, and the urea yield and Faraday efficiency bar graphs were plotted under a bias of 0.1 V vs. RHE.
[0025] Fig. 9 The Cu2O prepared in Example 1 of the present invention and the Cu2O@Cu1Co1 / NC prepared in Example 1 of the present invention are used as photocathodes, respectively, and the photocurrent density changes with time curve (jt) under 0.1V vs.RHE conditions. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention. Example
[0027] (1) Preparation of Cu(OH)2 nanorods The purchased copper sheets need to be processed as follows: First, cut the copper sheets into rectangles of 3 cm × 1 cm so that they can be used as supporting electrodes later; put the cut copper sheets into acetone, ethanol, secondary water, and hydrochloric acid solution (V 水 :V HCl =3:1) ultrasonic cleaning for 15 minutes, so as to remove organic matter, oxide layer and other impurities that may exist on the substrate surface; after the ultrasonic cleaning is completed, the copper sheet is rinsed with distilled water for 3 times to clean the hydrochloric acid solution remaining on the surface, and then placed in a vacuum drying oven to dry for use. The clean copper sheet, platinum sheet and Ag / AgCl electrode are used as the working electrode, counter electrode and reference electrode respectively, and 3M KOH solution is used as the electrolyte at 10mA / cm 2 The electrochemical oxidation was carried out at a constant current for 10 min. After the electrolysis, a blue Cu(OH)2 / Cu sheet was obtained, which was rinsed with distilled water and dried in a vacuum drying oven for later use.
[0028] (2) Preparation of Cu2O nanorods, comprising the following steps: The blue Cu(OH)2 / Cu sheet prepared above was first placed in a tube furnace, calcined in air at 180°C for 1 hour to convert into CuO, and then annealed at 600°C for 4 hours in an argon flow (purity 99.9995%). The temperature was naturally lowered to obtain a Cu2O / Cu sheet.
[0029] (3) Preparation of Cu2O@Cu1Co1 / NC, including the following steps: The Cu2O / Cu sheet prepared above was immersed in 20mL of an aqueous solution containing 0.1M dopamine hydrochloride, and the pH was adjusted to 9 with a 1.0M KOH solution. 37.5mg of 0.01M Cu(NO3)2 and 36.6mg of 0.01M Co(NO3)2 were added to the solution, and the film was formed by standing for 10min. The Cu2O / Cu sheet coated with copper-cobalt dopamine was taken out, washed and dried, and placed in a tube furnace, and calcined at 500℃ in an argon atmosphere for 1h to obtain Cu2O@Cu1Co1 / NC.
[0030] Photoelectrocatalytic CO2 / NO3 - Co-reductive coupling to urea A double-layer H-type electrolytic cell with a quartz window and a condensed water jacket was used. In a three-electrode system, the Cu2O@Cu1Co1 / NC nanorod array grown on the surface of a copper sheet was used as the photocathode, and the platinum sheet and Ag / AgCl electrode were used as the anode and reference electrode. Photoelectrocatalytic urea synthesis was tested in a mixed electrolyte of 0.1M KHCO3 and 0.05M KNO3 with CO2. A 300W xenon lamp with an AM 1.5G filter was used to simulate sunlight (light intensity 100mW·cm -2 ), test the linear scan curve (LSV) under the condition of illumination and without illumination, and select the appropriate bias voltage range according to the LSV under illumination and without illumination, and perform constant potential photoelectrolysis under different bias voltages. Subsequently, we used three quantitative test methods, colorimetry, high performance liquid chromatography, and nuclear magnetic resonance 1H spectroscopy, to detect the blank electrolyte (0.1M KHCO3) and the presence of CO2 / NO3 - Urea products after photoelectrolysis of (0.05M KNO3) electrolyte at 0.1V vs.RHE for 2h.
[0031] The quantification of urea is mainly carried out by colorimetry, while HPLC and 1H NMR spectroscopy are used as auxiliary results. The formation of urea, the main product of synchronous reduction, is determined by different test methods.
[0032] In the colorimetric method, urea product is quantified by the diacetyl monoxime method. The preparation method of the color developer is A: 100mL concentrated phosphoric acid, 300mL concentrated sulfuric acid and 600mL deionized water are mixed, and then 100mg ferric chloride is added; B: 5g diacetyl monoxime and 100mg semicarbazide are dissolved in 1000mL deionized water. The specific implementation method is to add 2mL color developer A and 1mL color developer B to 1mL electrolyte and mix them evenly. Then heat the above mixed solution to 100℃ and keep it warm for 15min, cool it to room temperature, and test its absorbance value at 525nm by UV-visible spectrophotometer.
[0033] The liquid chromatography was collected on an Agilent 1220 high performance liquid chromatograph. During the test, acetonitrile-water (70:30) was used as the mobile phase, and the electrolyte after the reaction was pumped into the Phenomenex NH2 column (250 mm × 4.6 mm) by high pressure infusion, and the flow rate was controlled at 0.3 mL min -1 After the components are separated in the chromatographic column, they automatically enter the detector for detection at a wavelength of 190nm. Liquid chromatography produces peaks based on the retention time of the substance, and the retention time of urea is about 11 minutes.
[0034] The spectroscopy was performed using a Bruker 400-MHz AVANCE III HD liquid NMR spectrometer. 1 H-NMR analysis: For each test, a mixture of 0.4 mL of the reacted electrolyte and 0.2 mL of dimethyl sulfoxide (DMSO) was used to prepare 1 The samples were analyzed by H-NMR.
[0035] Figure 1 (a) Scanning electron microscope analysis of Cu(OH)2 prepared in Example 1 revealed that Cu(OH)2 exhibited a nanorod structure.
[0036] Figure 1 (b) Scanning electron microscope analysis of the Cu2O prepared in Example 1 revealed that the Cu2O exhibited a nanorod structure.
[0037] Figure 2 The Cu2O@Cu1Co1 / NC catalytic electrode material prepared in Example 1 was analyzed by scanning electron microscope, and it was found that the Cu2O@Cu1Co1 / NC catalytic electrode material maintained the morphology of the nanorod array and the Cu2O structure ( Figure 2 (a)). In addition, the results of high-resolution transmission electron microscopy showed that the surface of Cu2O@Cu1Co1 / NC was coated with a dense carbon layer with a thickness of about 10 nm ( Figure 2 (b)).
[0038] Figure 3In order to perform X-ray diffraction analysis on Cu(OH)2, Cu2O and Cu2O@Cu1Co1 / NC prepared in Example 1, the positions and intensities of the main diffraction peaks of the three materials are consistent with their standard diffraction spectra. Figure 1 Correspondingly, XRD test results confirmed the successful preparation of Cu(OH)2, Cu2O and Cu2O@Cu1Co1 / NC nanorods. Among them, the XRD of Cu2O@Cu1Co1 / NC has a weak broad peak at around 20°, indicating the presence of graphite carbon.
[0039] Figure 4 In order to perform X-ray photoelectron spectroscopy analysis on the Cu2O@Cu1Co1 / NC prepared in Example 1 and study the surface composition and chemical state of the obtained product sample, the Cu 2p and N 1s high-resolution XPS spectra of the Cu2O@Cu1Co1 / NC catalyst are shown as follows: Figure 4 shown. Figure 4 The two peaks at 932.27 eV and 952.11 eV are attributed to Cu 2+ Cu 2p 3 / 2 and Cu 2p 1 / 2 The two peaks at 396.35eV and 399.73eV are attributed to pyridinic nitrogen and graphitic nitrogen. The XPS test results confirm that the Cu in Cu2O@Cu1Co1 / NC is mainly low-valent copper, and there is N element in the carbon layer, mainly graphitic nitrogen and pyridinic nitrogen.
[0040] Figure 5 To perform high-angle annular dark field imaging-scanning transmission electron microscopy analysis on the Cu2O@Cu1Co1 / NC prepared in Example 1. Given that the HAADF-STEM image of a single-atom material has a small area, in order to more intuitively see the single-atom situation on the Cu2O surface, we shortened the coating time (30 min) and coated a thinner layer of Cu1Co1 / NC on the Cu2O surface. Figure 5 In the figure, single atoms (bright spots) on the surface of the thinner areas of the Cu2O nanorods can be seen intuitively, and the single atoms are more distributed at the edges of the nanorods.
[0041] Figure 6 (a) The Cu2O@Cu1Co1 / NC prepared in Example 1 was subjected to photoelectric testing using a double-layer H-type photoelectrolysis cell equipped with a condensed water thermostat and a quartz window. The light power density was 100 mW cm -2 Photoelectric test equipment using simulated sunlight as the light source. A three-electrode system was used, with the Cu2O@Cu1Co1 / NC nanorod array grown on the surface of a copper sheet as the photocathode, a platinum sheet and an Ag / AgCl electrode as the anode and reference electrode, respectively, to conduct a photoelectrocatalytic urea synthesis test in a mixed electrolyte of 0.1M KHCO3 and 0.05M KNO3 with CO2 introduced.
[0042] Figure 6 (b) is the LSV graph of the Cu2O@Cu1Co1 / NC prepared in Example 1 in a mixed electrolyte of 0.1M KHCO3 and 0.05M KNO3 with CO2 flowing in the dark and light conditions. The LSV test results show that the Cu2O@Cu1Co1 / NC photocathode has a significant photoelectric response, and the photocurrent density of the photoelectric response is as high as 6mA·cm -2 .
[0043] Figure 7 (a) is the standard curve for the determination of urea by colorimetric method. The upper left and lower right photos show that Cu2O@Cu1Co1 / NC - After 2 h of photoelectrolysis in an electrolyte with a bias of 0.1 V vs. RHE, the product turned red, indicating that urea was generated.
[0044] Figure 7 (b) The upper and lower parts are respectively the quantitative detection of blank electrolyte (0.1M KHCO3) and the presence of CO2 / NO3 by HPLC and 1H NMR spectrometry. - The urea product after photoelectrolysis of (0.05M KNO3) electrolyte at 0.1V vs. RHE for 2h. The peak at 10.5min in HPLC and the peak at 5.7ppm in 1H NMR spectrum both prove the presence of CO2 / NO3 - After photoelectrolysis of (0.05M KNO3) electrolyte at 0.1V vs.RHE for 2h, urea was generated in the product.
[0045] Figure 8 The urea yield and Faraday efficiency bar graphs are shown for Cu2O prepared in Example 1 and Cu2O@Cu1Co1 / NC prepared in Example 1 as photocathodes at 0.1V vs.RHE. The urea yield of Cu2O@Cu1Co1 / NC as a photocathode at 0.1V vs.RHE is 34.6µg·h -1 cm -2 , the Faraday efficiency is 24.3%. The urea yield of Cu2O as photocathode is 5.7µg·h at 0.1V vs.RHE. -1 cm -2 , and the Faraday efficiency is 4.1%. From the comparison of the yield and Faraday efficiency of photoelectrocatalytic urea synthesis, Cu2O@Cu1Co1 / NC is obviously better than Cu2O.
[0046] Fig. 9The graphs of the photocurrent density variation over time under 0.1V vs. RHE conditions for Cu2O prepared in Example 1 and Cu2O@Cu1Co1 / NC prepared in Example 1 as photocathodes are shown. The test results show that the stability of Cu2O is less than 1h, while the stability of Cu2O@Cu1Co1 / NC is greater than 10h, and the stability of Cu2O@Cu1Co1 / NC is greatly improved.
[0047] In summary, the catalyst electrode material Cu2O@Cu1Co1 / NC prepared in the embodiment of the present invention has good photoelectrocatalytic performance of CO2 / NO3 - Co-reduction coupling to produce urea performance.
[0048] Although the present invention has been described in detail by referring to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention. Therefore, the scope of protection of the present invention shall be subject to the scope of protection described in the claims.
Claims
1. A copper-cobalt modified photocathode, characterized in that: The photocathode is Cu2O@Cu1Co1 / NC catalytic electrode material.
2. A method for preparing a photocathode as claimed in claim 1, characterized in that: The following steps are involved: (1) Use clean copper sheet, platinum sheet and Ag / AgCl electrode as working electrode, counter electrode and reference electrode respectively, and use 3M KOH solution as electrolyte at 10 mA / cm 2 The electrochemical oxidation was carried out at a constant current for 10 min. After the electrolysis, a blue Cu(OH)2 / Cu sheet was obtained, which was washed with distilled water and dried in a vacuum drying oven for later use. (2) The blue Cu(OH)2 / Cu sheet prepared above was first placed in a tube furnace and calcined in air at 180°C for 1 hour to convert into CuO, and then annealed at 600°C for 4 hours in an argon flow (purity 99.9995%) atmosphere; the temperature was naturally lowered to obtain a Cu2O / Cu sheet; (3) The Cu2O / Cu sheet prepared above was immersed in 20 mL of an aqueous solution containing 0.1 M dopamine hydrochloride, the pH was adjusted to 9 with a 1.0 M KOH solution, 0.01 M Cu(NO3)2 and 0.01 M Co(NO3)2 were added to the solution, and the solution was allowed to stand for 10 min to form a film; the Cu2O / Cu sheet coated with copper-cobalt dopamine was taken out, washed and dried, and placed in a tubular furnace, and calcined at 500 °C in an argon atmosphere for 1 h to obtain Cu2O@Cu1Co1 / NC.
3. The preparation method according to claim 2, characterized in that: In the step (1), the copper sheet is sequentially placed in acetone, ethanol, secondary water, and hydrochloric acid solution for ultrasonic cleaning for 15 minutes; after the cleaning is completed, the copper sheet is rinsed with distilled water for 3 times and then dried in a vacuum drying oven.
4. The preparation method according to claim 2, characterized in that: The molar ratio of Cu(NO3)2 and Co(NO3)2 is 1:10~10:
1.
5. An electrolytic cell comprising the photocathode as claimed in claim 1, characterized in that Cu2O@Cu1Co1 / NC was used as the photocathode, platinum sheet as the anode, Ag / AgCl electrode as the reference electrode, and a mixture of 0.1M KHCO3 and 0.05M KNO3 containing CO2 as the electrolyte.
6. A method of catalyzing CO2 / NO3 using the electrolytic cell as claimed in claim 5 - Reductive coupling for the application of urea.
7. The use according to claim 6, characterized in that Cu2O@Cu1Co1 / NC was used as the photocathode, platinum sheet as the anode, Ag / AgCl electrode as the reference electrode, and the light intensity was 100 mW·cm -2 The product urea was obtained by irradiating a mixture of 0.1M KHCO3 and 0.05M KNO3 containing CO2 with light.
Citation Information
Cited By
Unbiased coupling photoelectrochemical system and preparation method and application of anode and cathode of unbiased coupling photoelectrochemical system
CN120738701A